2018
DOI: 10.3390/molecules23040870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lignans from Schisandra chinensis Rattan Stems against Aβ1-42-Induced Memory Impairment in Rats and Neurotoxicity in Primary Neuronal Cells

Abstract: Oxidative stress, which is caused by Amyloid-β deposition in brain, plays an important role in Alzheimer’s disease. In this study, we found that lignans from Schisandra chinensis rattan stems (rsSCH-L) could reduce the escape latency and the distance travelled by the Aβ1–42 injected rats while the crossing platform time was enhanced in the Morris water maze test. Further research demonstrated that lignans from rsSCH-L attenuated Aβ1-42-induced neuronal cell injury by increasing the content of SOD and GSH-Px an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Dibenzocyclooctadiene lignans isolated from S. chinensis exhibit anti-inflammatory and antioxidant properties, as well as improving cognitive functions (e.g., memory) [ 77 ]. In addition, prior studies have reported that S. chinensis fruit extracts—in which the major bioactive constituents are lignans—exert a neuroprotective effect and possess bioactivity which may help prevent Alzheimer’s Disease [ 78 ]. Furthermore, S. chinensis fruit may have positive effects on the liver, as well as on the gastrointestinal, immune, sympathetic and central nervous systems [ 79 , 80 ].…”
Section: Lignan Content Of Various Regional Dietsmentioning
confidence: 99%
“…Dibenzocyclooctadiene lignans isolated from S. chinensis exhibit anti-inflammatory and antioxidant properties, as well as improving cognitive functions (e.g., memory) [ 77 ]. In addition, prior studies have reported that S. chinensis fruit extracts—in which the major bioactive constituents are lignans—exert a neuroprotective effect and possess bioactivity which may help prevent Alzheimer’s Disease [ 78 ]. Furthermore, S. chinensis fruit may have positive effects on the liver, as well as on the gastrointestinal, immune, sympathetic and central nervous systems [ 79 , 80 ].…”
Section: Lignan Content Of Various Regional Dietsmentioning
confidence: 99%
“…They were also reported to reduce hunger, delay aging, increase vitality, and improve mental health [ 4 ]. They demonstrate neuro and hepato-protective, anti-inflammatory, antioxidative, detoxification, immunostimulant, antiviral, and anti-cancer activities, as well as cardiovascular and skin-protective properties [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gomisin A (Gom A, wuweizichu B, wǔwèizi chún yĭ), a dietary dibenzocyclooctadiene lignan compound isolated from the hexane of Schisandra chinensis fruit extract [ 1 , 2 , 3 , 4 , 5 , 6 ], has been increasingly demonstrated to have anti-inflammatory, anti-oxidative, antihypertensive, neuroprotective, and anti-proliferative properties [ 7 , 8 , 9 , 10 , 11 ]. For example, this compound was reported to induce protective effects either against hepatic and renal injury induced by CCl 4 exposure, or nitropropionic acid-induced striatal toxicity, through differential regulation of the MAPK signal transduction pathway [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ability of crude Schisandra chinensis extracts to perturb the function of hypothalamic-pituitary-adrenal and gonadal axis in stressed rats has been previously reported [ 20 , 21 ]. The extracts of S. chinensis or arisanensis have been noticed to improve either amyloid-β- and scopolamine-induced cognitive impairment or pancreatic β-cell function [ 9 , 10 , 22 , 23 , 24 , 25 ]. Of particular interest, an earlier study demonstrated the effectiveness of crude S. chinensis extract in decreasing prolactin production in pituitary GH 3 cells, suggesting that such an extract could be therapeutically beneficial for patients with hyperprolactinemia and prolactinoma [ 26 ].…”
Section: Introductionmentioning
confidence: 99%